2018
DOI: 10.1177/0300060518789817
|View full text |Cite
|
Sign up to set email alerts
|

Dose-response effects of omega-3 on platelet aggregation: an observational study

Abstract: Objective This study aimed to evaluate the dose-response effects of supplemental omega-3 fatty acids on platelet function in healthy volunteers. Methods Twelve healthy volunteers ingested a normal supplemental dose of 1260 mg omega-3 fatty acids daily for 5 days, followed by a high dose of 2520 mg daily for another 5 days. Multiple electrode aggregometry (MEA) with four different agonists was used to measure platelet aggregation before and after the normal- and high-dose regimes. In vitro spiking using physiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…2). However, it must be stated that every individual value of ASPI AUC (without ASA) following Omega-3 intake was within normal MEA reference range [24,26,27], whereas some were below the reference value before Omega-3 intake (see below). Also, in the ASPI assays with both low and high dose ASA, all but 1 volunteer were below 30 U AUC (the exception having an AUC of 32 U in the ASPI+ASAx10 assay) following treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2). However, it must be stated that every individual value of ASPI AUC (without ASA) following Omega-3 intake was within normal MEA reference range [24,26,27], whereas some were below the reference value before Omega-3 intake (see below). Also, in the ASPI assays with both low and high dose ASA, all but 1 volunteer were below 30 U AUC (the exception having an AUC of 32 U in the ASPI+ASAx10 assay) following treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ADP is an important agonist which induces platelet aggregation through the membrane-bound P2Y 12 -receptor by indirectly increasing the cytosolic calcium-level (Ca 2+ ) and thereby enable the complex formation of GpIIb/IIIa [45]. However, some studies show the contrary, indicating a negligible effect on ADP-induced platelet aggregation in the presence of Omega-3 fatty acids [27,46].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other effects of EPA/DHA include protection against CVD by reducing serum triacylglycerides (TAG) 79 , heart rate 80 , blood pressure (BP) 81 , and serum homocysteine levels 82 , as well as regulating and resolving inflammatory process 83 as shown in randomized trials with fish oil supplementation. However, other reports have shown that omega-3 have no effect on platelet aggregation 84 . Despite so, there is a paucity of available data on yellow stripe scad (YSS) as a source of omega-3 fatty acid in overweight healthy subjects.…”
Section: Modulation Effects Of Fish Fillet (Epa and Dha) On Platelet mentioning
confidence: 91%